Investigating Determinants of SMEs’ Green Practices: A Literature Review and Proposed Model - Ernawati, Erni; Fauziana, Diyah Ratna (Indonesian Journal of Sustainability Accounting and Management, 2025)
This study aims to identify the drivers of green practices, the types of green practices employed, and the green performance of small and medium-sized enterprises (SMEs) using a systematic literature review approach. Three stages of the Preferred Reporting Items for Systematic Reviews and Meta- Analysis (PRISMA) Protocol were carried out, involving 37 empirical-based articles. These articles were selected from a total of 2,662 documents gathered from the Scopus and ProQuest databases based on the objectives of this study. The content analysis method was employed to identify themes related to green drivers, practices, and performance, which were used to develop the model as the study’s proposition. The green drivers of SMEs’ green practices include green entrepreneurship orientation, green market orientation, green regulations, and green relational motives. The implemented green practices encompass green marketing, procurement, operations, logistics and transportation, human resource management, innovation, and product design. Green performance comprises economic, social, and environmental aspects. The proposed model is subject to validation in future research to clarify the drivers of green practice in SMEs that contribute to their sustainable business performance. The results of this study are beneficial for improving a firm’s green performance by implementing relevant green practices within the organization.